2017
DOI: 10.1093/brain/awx181
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic consistencies across epilepsies: a stereotactic-EEG informed high-resolution structural connectivity study

Abstract: See Bernasconi (doi:10.1093/brain/awx229) for a scientific commentary on this article. Drug-resistant localization-related epilepsies are now recognized as network diseases. However, the exact relationship between the organization of the epileptogenic network and brain anatomy overall remains incompletely understood. To better understand this relationship, we studied structural connectivity obtained from diffusion weighted imaging in patients with epilepsy using both stereo-electroencephalography (SEEG)-determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
82
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(94 citation statements)
references
References 94 publications
11
82
0
Order By: Relevance
“…A recent study of coregistered of intracranial EEG information with diffusion MRI–derived structural connectome data across a cohort of patients with temporal and extratemporal foci. The study suggested a divergence of connectivity patterns in epileptogenic compared to nonepileptogenic areas, with epileptogenic networks displaying more intact local connectivity while whole brain connectivity strength seemed to be reduced . The biologic implications of these data are not yet clear.…”
Section: Clinical Connectomicsmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study of coregistered of intracranial EEG information with diffusion MRI–derived structural connectome data across a cohort of patients with temporal and extratemporal foci. The study suggested a divergence of connectivity patterns in epileptogenic compared to nonepileptogenic areas, with epileptogenic networks displaying more intact local connectivity while whole brain connectivity strength seemed to be reduced . The biologic implications of these data are not yet clear.…”
Section: Clinical Connectomicsmentioning
confidence: 91%
“…The study suggested a divergence of connectivity patterns in epileptogenic compared to nonepileptogenic areas, with epileptogenic networks displaying more intact local connectivity while whole brain connectivity strength seemed to be reduced. 73 The biologic implications of these data are not yet clear.…”
Section: Clinical Connectomicsmentioning
confidence: 99%
“…46 Additional intracranial connectivity measures have also revealed increased connectivity in epileptogenic networks when compared to regions outside of the epileptogenic zone. 47 To further explore computational mechanisms of seizure dynamics, it has been speculated that local clusters of neurons may isolate themselves from the rest of the network, likely through an imbalance between local and distant connections, a mechanism described as "network tightening". 48 Under this account, however, functional isolation of the seizure-onset zone was speculated to play a role in annihilating epileptogenic activity and, as such, may represent a potential compensatory mechanism through which locally confined, seizure-related activity is prevented from spreading.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, whilst minimizing false positives, the stringent-but necessary-statistical approach incorporated into VBM could obscure subtle common structural alterations (Keller & Roberts, 2008). Furthermore, a recently published study has shown that pathological structural connectivity causes disturbances to common large-scale functional brain networks regardless of the localization of the epileptogenic zone in patients with refractory focal epilepsy (Besson et al, 2017). One issue to therefore consider is that patients with NDfE have heterogeneous neurobiological mechanisms and different epileptogenic foci, which would not be identified using a technique such as VBM that is used to detect abnormalities common to a patient group.…”
Section: Biological and Clinical Implicationsmentioning
confidence: 99%
“…Particular anatomical circuits act as critical modulators of seizure generation and propagation, and seizure activity does not spread diffusely throughout the brain but propagates along specific anatomical pathways, regardless of the localization of the brain insult (Loscher & Ebert, 1996;Piredda & Gale, 1985). Furthermore, a recently published study has shown that pathological structural connectivity causes disturbances to common large-scale functional brain networks regardless of the localization of the epileptogenic zone in patients with refractory focal epilepsy (Besson et al, 2017). Moreover, particular deep brain regions-such as the thalamus and thalamocortical pathways-play a crucial role in the clinical expression of seizures in the epilepsies (Dreifuss et al, 2001), and anatomically support widespread distributed cortico-subcortical networks (Nieuwenhuys, Voogd, & Huijzen, 1988)-are structurally and physiologically abnormal in both hemispheres in patients with long-standing focal and generalized epilepsy disorders (Bonilha et al, 2013;He, Doucet, Sperling, Sharan, & Tracy, 2015;Kay & Szaflarski, 2014;Keller et al, 2014Keller et al, , 2015Kim et al, 2014;O'Muircheartaigh et al, 2012).…”
Section: Biological and Clinical Implicationsmentioning
confidence: 99%